Farmer and Veterinary Practices and Opinions Related to Fertility Testing and Pregnancy Diagnosis of UK Dairy Cows - Tzelos, Thomas; Howes, Natalie L.; Esteves, Cristina L.; Howes, Martin P.; Byrne, Tim J.; Macrae, Alastair I.; Donadeu, Francesc X. (Frontiers in Veterinary Science, 2020)
Dairy cow farming plays an important role in the UK and worldwide economies. Significant challenges are currently being faced regarding sustainability of the dairy industry. Dairy cow subfertility remains an important issue limiting herd productivity, resulting in annual losses of hundreds of millions of pounds in the UK alone. To address this, accurate monitoring of reproductive status and early detection of fertility issues in individual cows is essential. The aim of this study was to gather farmer and veterinarian opinions on current practices and perceived gaps related to diagnosis of fertility issues and pregnancy testing in UK dairy farms. Using online questionnaires, data were collected and analysed from a total of 40 farmers and 59 veterinarians. The results showed that non-seen bulling checks and ultrasound were the most frequent tools to detect fertility issues, and that most farmers tested post-calving, and often again before or during mating. Most farmers believed that current tests did not meet their expectations, with half of those being willing to pay more than they were currently paying for fertility testing. In regard to pregnancy testing, ultrasound was most commonly used, at 30-50 days post-insemination either in individual or groups of cows. Again, most farmers believed that current tests did not meet their expectations, and a majority would consider paying a higher cost for a test that was better than those currently available. In addition, a majority of farmers would consider using a test that could detect pregnancy within 2 weeks post-insemination, if such test existed, because they believed it would help improve their herds’ reproductive performance. Overall, the opinions of farmers and veterinarians indicate that there is significant scope for improving dairy herd fertility monitoring practices in the UK, through development of improved assays that can diagnose pregnancy and infertility earlier, are less disruptive to farm operations and are more cost effective than available tools. They also provide useful information to guide the future development and implementation of better diagnostics for improving reproductive performance of dairy cattle.